PENGARUH PENGGUNAAN HYPNOTEACHING PADA PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS VII SMPN 2 UTAN TAHUN PELAJARAN 2015/2016 - Aminah, Siti; Nissa, Ita Chairun; Juliangkary, Eliska (Media Pendidikan Matematika, 2017)
This study aims to determine the effect of using hypnoteaching on problem based learning toward the students learning outcomes at VII grade studen of SMPN 2 Utan. The Type of research is a eksperimental research. The population of this research includes all students of class VII SMPN 2 Utan. The sampling technique used purposive sampling. The class VII2 as the experimental class Â and class VII 4 as the control class. The data collection is done by using about pre-test and post-test form. Data processing is done by statistical analysis. The results showed that t_count = 2.17 is greater than t_table = 2.001. so it can be concluded that the hypothesis is rejected Ho and Ha accepted. That Â means that the treatment given to the experimental group have an influence towars the student learning outcomes using model hypnoteaching on problem based learning at VII grade student of SMPN 2 Utan